Produccion in vitro de acido lactico a partir de sangre bovina - Ortiz, F.=700 1 Bell, L.
(En, Es)
Ilus., 15 ref.
Keywords: CULTIVO IN VITRO; ACIDO LACTICO; PRODUCCION; TEMPERATURA; GLUCOSA; INSULINA; GLUCAGON; SANGRE; GANADO BOVINO; CUBA